PENGARUH MODIFIED ATMOSFER PACKAGING DENGAN PLASTIK POLYETHYLENE (PE) TERPERFORASI TERHADAP MUTU FISIK CAISIM (BRASSICA JUNCEA) SELAMA PENYIMPANAN PADA SUHU DINGIN - Nocianitri, Komang Ayu; Rina Pratiwi Pudja, Ida Ayu (Agrotekno; Vol 13, No.2 Agustus 2007)
Water loss is a main cause of deterioration because it results not only in direct quantitative losses, but also in losses in appearance (wilting and shriveling), textural quality (softening, flaccidity, limpness, loss of crispness and juiciness), and nutritional quality. Transpiration is a physical process that can be controlled by applying treatment to commodity e.g. waxes or wrapping with plastic film or by manipulating the environment. Temperature management is the most effective tool for extending the shelf life of fresh horticultural commodities. The aimed of this experiment was to study the effect of modified atmosphere packaging of polyethylene (PE) plastic on physical quality of caisim during cooling storage. For that experiment, caisim were packed into PE plastic without hole (P1), 2 holes (P2), 4 holes (P4), 6 holes (P6), and 8 holes (P8). Products as controls were provided without packed. Then, products were stored in cold storage on 0 – 5oC for 4 days. The results of this experiment shows that packaging were significantly affected the decreasing of weight, moisture content, and the value of physical quality of caisim for 4 days, in spite of colors. Packaging of polyethylene plastic without hole can delay the deterioration or change physical quality of caisim more than 4 days.
Keywords: caisim, polyethylene plastic, physical quality